LOVE, MEMORY, AND POETRY IN ALEKSANDR FAYNBERG’S POEM - Zoirova Diyora, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Introduction. Aleksandr Faynberg is a famous 20th-century poet. His poems often talk about human feelings, love, memory, and life experiences. In the selected poem, the poet reflects on love that leaves pain, memories that sometimes stay and sometimes fade, and how writing poetry can help keep these feelings alive. This poem shows that people often remember some words, moments, or people, while forgetting others. Faynberg explains how love and memory affect a person over time and how poetry can help preserve emotions. The main goal of this article is to study Faynberg’s poem and explain the main ideas, emotions, and messages in a simple and clear way. It also looks at how memory, love, and writing are connected in the poem.